Characterization of polyphenols compounds extracted from stressed apple peel and their interaction with β-lactoglobulin - Emilce E. Llopart; Roxana A. Verdini; Néstor J. Delorenzi; Pablo A. Busti (Heliyon, 2023)
This paper proposes to apply a postharvest environmental stress to red apples, Malus domestica, variety Red Delicious in order to increase the polyphenols compounds (PP) content in their peels. The possibility of enhancing extractable PP provides a useful alternative for the use of discarded crops in the food industry. A great increase in PP was observed in response to light damage produced by the environmental stress applied in this work. Flavonols > anthocyanins > flavanols > dihydrochalcones > phenolic acids is the order in PP content. The interaction of the extracted PP from unstressed and stressed apple peels with beta-lactoglobulin (β-LG) was characterized. A PP/β-LG complex which was formed with one single binding site in the protein was determined. The interaction was spontaneous and enthalpy driven. PP extracted from unstressed samples had greater affinity for the protein than PP extracted from stressed samples, possibly due to the polar characteristic of anthocyanins. The results of this last study could provide a better understanding of the interaction between PP and β-LG to incorporate them into functional foods.